Synthesis and Analysis of PZT Using Impedance Method of Reactance Estimation - Witsarut Sriratana; Riichi Murayama; Lerdlekha Tanachaikhan (My University, 2013)
This study presents an analysis of equivalent circuit namely Butterworth Van Dyke (BVD) [1,2] by using impedance method to stimulate Zirconate Titanate (Piezoelectric ceramic) which is initially synthesized from Lead Oxide (PbO), Zirconium Dioxide (ZrO2) and Titanium Dioxide (TiO2) and vibrated in thickness mode. The reactance was estimated in the frequency range lower than the resonance frequency and then compared to the impedance obtained from measurement using impedance analysis machine model HP4192A and HP4194 [3]. The results from HP4194 were analyzed for BVD parameters: Motional resistance (R1), Inductor (L1), Capacitor (C1), and Capacitor corresponds to the electrostatic capacitance (Co). Another accuracy analysis was compared by the calculation results using the method of IEEE 176-1987 [4] to the impedance values measured by HP4192A. In this study, there were two conditions for experiment and consideration of parameter variation in BVD equivalent circuit: variation of temperature and mechanical force. These parameters are evaluated to design the efficient circuit for PZT utilization to obtain the optimal efficiency.
Keywords: Reactance; Lead zirconate titanate; Ceramic capacitor; Ferroelectric and Piezoelectric Materials